Sex differences in clinical outcomes and biological profiles in systemic sclerosis-associated interstitial lung disease: a post-hoc analysis of two randomised controlled trials. (October 2022) - Volkmann, Elizabeth R; Tashkin, Donald P; Silver, Richard; Bostwick, Carol Feghali; Assassi, Shervin; Baker Frost, DeAnna; Leng, Mei; Wilhalme, Holly; Kim, Grace Hyun; Goldin, Jonathan; Roth, Michael D
Summary: Background: Observational studies have shown that men with systemic sclerosis have an increased risk of interstitial lung disease (ILD) and mortality compared with women. However, previous studies have not controlled for treatment effect or evaluated the biological mechanism or mechanisms underlying this sex difference. We aimed to compare ILD progression and long-term morbidity and mortality outcomes in male and female participants of two randomised controlled trials for systemic sclerosis-associated ILD. Methods: For this post-hoc analysis, data from all participants in the Scleroderma Lung Study (SLS) I and SLS II were analysed. The primary objective was to explore the effect of sex on the course of the percentage predicted forced vital capacity (FVC) during and after active treatment over the 24-month study periods. In SLS I, 158 participants (111 women, 47 men) were randomly assigned to receive oral cyclophosphamide (cyclophosphamide; ≤2 mg/kg daily) or placebo; in SLS II, 142 participants (105 women, 37 men) were randomly assigned to receive oral mycophenolate mofetil (1500 mg twice daily) or oral cyclophosphamide (≤2 mg/kg daily). Sex (ie, male or female) was self-reported in both studies by the participants. Changes in radiographic fibrosis and time to death and respiratory failure were secondary outcomes of the present analysis. Baseline levels of biomarkers implicated in the pathobiology of systemic sclerosis-associated ILD were measured in bronchoalveolar lavage fluid in SLS I. Findings: In the SLS I placebo group, the rate of decline in percentage predicted FVC from 3 months to 12 months was greater in men than in women, but the difference was not significant (estimated effect –0·29 [95% CI –0·67 to 0·10]; p=0·14). In SLS II, the rate of decline in percentage predicted FVC from 3 months to 12 months was significantly worse in men treated with either cyclophosphamide (estimated effect –0·72; [95% CI –1·14 to –0·31]; p=0·00060) or mycophenolate mofetil (estimated effect –0·34 [–0·58 to –0·10]; p=0·0051) than in women. A greater proportion of men had a decline in percentage predicted FVC of 10% or greater compared with women for the pooled active treatment groups from SLS I and SLS II and the placebo group of SLS I. Men had worse radiographic outcomes at 2 years than women in SLS II, even after adjusting for baseline disease severity and treatment arm assignment. Long-term survival was worse in men in SLS I (log-rank test p=0·080) and SLS II (log-rank test p=0·030). In SLS II, male sex was independently associated with increased mortality (hazard ratio 2·42 [95% CI 1·16 to 5·04]; p=0·018). In bronchoalveolar lavage fluid, men had increased concentrations of pro-fibrotic mediators (eg, matrix metalloproteinase-13 and tissue inhibitor of metallopeptidase 1), whereas women had increased pro-inflammatory mediators (eg, interleukin [IL]-12, IL-7, and granulocyte-colony stimulating factor). Interpretation: In two randomised controlled trials, men with systemic sclerosis-associated ILD had a less favourable course of ILD both with and without active treatment, as well as worse long-term survival. Sex differences in pro-fibrotic or inflammatory mediators of disease might account for these differences and warrant future study. Funding: US National Institutes of Health; US National Heart, Lung, and Blood Institute; US National Institute of Arthritis and Musculoskeletal and Skin Diseases; Bristol Myers Squibb; and Hoffmann-LaRoche.